Maritime cyber threats and challenges - Pinko, Eyal (2020)
The maritime trade becomes crucial for countries' economy, security and sovereignty. Side by side to the growth of shipping, the vessels themselves and the sea-ports become more and more sophisticated, advanced and controlled by computerized and automated systems. Most of the maritime industry companies (from sea ports to shipping companies) are not ready and protected enough against cyber-attacks. Furthermore, there are no world regulation for the maritime industry yet, although the IMO (International Maritime Organization) is working on regulation that will fit the maritime industry, focusing on vessels. The IMO regulation is expecting to be implemented during 2021.
Abstract.
Keywords: Pomorska industrija -- Pomorska trgovina -- Cyber sigurnost -- Cyber napadi -- Morske luke